Tākwīnu āl-Bī’āh āl-Lughāwiyyāh ās-Sām’iyyāh āl-Bāshoriyyāh lī āt-Tholibāt āl-Jādidāt fīī āl-Fāshl āl-Awwāl bīī Mā’hādi Dārissālām Gontor Ngawi - Mely Puspitaningrum; Moh. Ismail; Agus Budiman; Siti Safira Al-latifatuzzahra; Salsabila Rizqi Amaliana (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This research is motivated by the results of a researcher survey at Pondok Modern Darussalam Gontor which applies language environment in its daily activities aims to create a language environment so familiar that it integrates all aspects of female students daily activities into the official language environment system. This environment will encompass the elements of education and teaching that the students can perceive, hear, and feel. This research aims to: Knowing the implementation of language environment in Pondok Modern Darussalam, Knowing the non-formal extracurricular supporting activities that form language environment, and Knowing the inhibiting factors in the implementation of language environment at Pondok Modern Gontor. To achieve these objectives, descriptive qualitative research with field research method is used. The subjects in this study were the head master of the boarding school, the language department stuff, teacher, responsible of dormitory, and the student. Data were collected through participatory observation, in-depth interviews, and documentation, then the data were analyzed and conclusions were drawn. The conclusions that can be drawn from this study are: first; the implementation of language environment is by requiring the use of Arabic for 24 hours a day, in learning full of language so that students are accustomed to using Arabic. Second; language environment is very instrumental in improving the language skills of students, with language habituation inside and outside the classroom they are able to communicate Arabic fluently. Third; The supporting factors are the existence of a supportive environment, cooperation, competent Arabic language educators, and adequate infrastructure. The conclusion from the results of this research is that the formation of an Arabic language environment accompanied by extracurricular events can influence female students in the learning process and absorption of Arabic in their lives. For future researchers, they can develop their learning strategies and Researchers suggest that further research emphasizes implementation and focuses on improving the achievement of the values of good Arabic learning goals by maximizing the effectiveness of the extracurricular Arabic language events that have been held. focus on increasing the achievement of the values of the ultimate goal of good Arabic language learning by maximizing the effectiveness of the running of extracurricular Arabic language events that have been held.